Accuracy requirements on intrinsic alignments for Stage-IV cosmic shear - Paopiamsap, A; Porqueres, N; Alonso, D; Harnois-Deraps, J; Leonard, CD (Maynooth Academic Publishing, 2024)
In the context of cosmological weak lensing studies, intrinsic alignments (IAs) are one of the most In the context of cosmological weak lensing studies, intrinsic alignments (IAs) are one of the most complicated astrophysical systematic\rev{s} to model, given the poor understanding of the physical processes that cause them. A number of modelling frameworks for IAs have been proposed in the literature, both purely phenomenological or grounded on a perturbative treatment of symmetry-based arguments. However, the accuracy with which any of these approaches is able to describe the impact of IAs on cosmic shear data, particularly on the comparatively small scales ([Math Processing Error]) to which this observable is sensitive, is not clear. Here we quantify the level of disagreement between the true underlying intrinsic alignments and the theoretical model used to describe them that can be allowed in the context of cosmic shear analyses with future Stage-IV surveys. We consider various models describing this "IA residual’', covering both physics-based approaches, as well as completely agnostic prescriptions. The same qualitative results are recovered in all cases explored: for a Stage-IV cosmic shear survey, a mis-modelling of the IA contribution at the [Math Processing Error] level produces shifts of [Math Processing Error] on the final cosmological parameter constraints. Current and future IA models should therefore aim to achieve this level of accuracy, a prospect that is not unfeasible for models with sufficient flexibility.